F.l.t.r.(front row): Brown, Brandt, Wilson, Krag, Erlander and Sjarett. Last row: Grüter, Suurhoff, Vondeling, Pittermann, Carglia and Bratteli
F.l.t.r.(front row): Brown, Brandt, Wilson, Krag, Erlander and Sjarett. Last row: Grüter, Suurhoff, Vondeling, Pittermann, Carglia and Bratteli.